High Strain Rate Characteristics of Nanoparticle Modified Blast Energy Absorbing Materials. (2016) - Drdlová, Martina; Prachař, Vladan
Abstract: Due to explosion, and insufficient energy absorbing capabilities of civil building structures, many structures collapsed, which can be connected with losses of human lives and properties. One way how to improve the blast resistance of the structure is using of sacrificial cladding structures with the core made of high blast absorbing material. Foams based on lightweight porous particles and resins are materials with high potential of impact energy absorption. This article describes the mechanical properties of the foams reinforced with carbon nanofibers and nanotubes. Specific porous lightweight foam with high volume fraction of microspheres (70 vol.%) was prepared and modified by 1–5 vol.% of multi-wall carbon nanotubes and nanofibers (separately). The compressive and flexural strength tests were conducted at quasi-static load. Split Hopkinson Pressure Bar apparatus was used to obtain high velocity characteristics of the materials. The relative absorbed energy was calculated to assess the relation between the composition of the material and its shock wave attenuation capacity. The mixtures containing carbon nanofibers exhibited an increasing trend in the energy absorption capacity with increasing nanoparticle content up to 4 vol.%. The addition of carbon nanotubes also increased absorbed energy (again up to 4 vol.%, crossing this concentration, the significant drop was observed). Comparing the values of the relative absorbed energy, the carbon nanofibers composites prevail over the nanotubes modified ones.